Oxytetracycline and Gentamicin: Two Clinically relevant Antimicrobials Widely Used by Costa Rican Farmers. Implications of Their Use Outside Clinical Cettings and Request for Action - Rodríguez Sánchez, César (2008)
This mini-review deals with oxytetracycline and gentamicin: two clinically-relevant antimicrobials that find extensive usage in horticulture and other productive activities. The manuscript begins with a few words on their mechanism of action and clinical utility. Thereafter I address the most important mechanisms of acquired or intrinsic resistance described to date and some implications of the unrestricted use of these drugs outside clinical settings. A number of reports on the occurrence of antimicrobial-resistance genes and antimicrobial-resistant bacteria in agroecosystems illustrates that a threat exists and justifies the plea for monitoring programs and environmental risk assessments with which the article concludes.